Strengthening the Online Registration System as an Effort to Improve Public Understanding Effort to Improve Public Understanding at Colomadu 2 Health Center - Herawati, Prianggi; Kresno, Ario; Agnes, Prawisty (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Background: As technology and communications develop increasingly sophisticated and rapidly, the unlimited flow of information becomes more easily accessible, making technology a necessity for humans in carrying out all daily activities. This is also accompanied by changes in times that are increasingly rapid and limitless, bringing world civilization. In this era, all activities are carried out by utilizing the existence of technology, which prioritizes automation processes and direct data exchange in the form of connectivity between humans, machines and data included in the Internet of Things and Artificial Intelligence with a combination of robotic and sensor technology using the existence of the internet as a link. Information and communication technology is the backbone of the revolutionary movement. Objective: . The general aim of this community service activity is to increase the understanding of the Colomadu 1 Community Health Center regarding the online registration system for accessing information on the Online Registration Application. Method: This community service activity method uses socialization methods, question and answer tutorials and evaluation. Results: This research shows that the average community understanding after education on strengthening the online registration system (Mean= 68.08; SD=6.80) is greater than the average understanding score before education (Mean+ 80.00; SD=7.82), and this is statistically significant (p<0.001).